Composite Second-Order Sliding Mode and Backstepping Control for Power Pulsation Suppression in Dynamic Wireless Charging - Behnamfar, Milad; Olowu, Temitayo O.; Tariq, Mohd; Debnath, Anjan; Sarwat, Arif (IEEE transactions on industry applications, 2024)
This paper presents a novel composite control scheme aimed at ensuring stable and consistent output power in dynamic wireless charging (DWC) systems subject to mutual coupling variations caused by electric vehicle (EV) movement. The proposed control strategy combines backstepping control and second-order sliding mode control, offering both finite-time stability and large-signal stability. The finite-time stability property enhances control robustness and improves disturbance rejection capability, while the large-signal stability feature enables the controller to effectively handle significant disturbances. Furthermore, this paper presents a detailed design procedure for the proposed composite control method, along with stability analysis to demonstrate its finite-time stability property. Simulation and experimental results confirm the effectiveness of the proposed composite controller in stabilizing power at the reference value despite mutual coupling variation and load changes, minimizing fluctuations to just 0.1%. Additionally, the proposed controller consistently maintains an efficiency of 84% across varied positions as the vehicle moves over the transmitter coils.